ILEAL ATRESIA WITH DUPLICATION CYST OF TERMINAL ILEUM: A RARE ASSOCIATION - Sinha S; Sarin YK; Ramji S (EL-Med-Pub, 2012)
A case of ileal atresia in association with duplication of terminal ileum is being reported here.